Characteristics and outcomes of ambulatory patients with suspected COVID-19 at a respiratory referral center. (June 2022) - Guntur, Vamsi P.; Modena, Brian D.; Manka, Laurie A.; Eddy, Jared J.; Liao, Shu-Yi; Goldstein, Nir M.; Zelarney, Pearlanne; Horn, Carrie A.; Keith, Rebecca C.; Make, Barry J.; Petrache, Irina; Wechsler, Michael E.
Abstract: Rationale: SARS-CoV-2 continues to cause a global pandemic and management of COVID-19 in outpatient settings remains challenging. Objective: We sought to describe characteristics of patients with chronic respiratory disease (CRD) experiencing symptoms consistent with COVID-19, who were seen in a novel Acute Respiratory Clinic, prior to widely available testing, emergence of variants, COVID-19 vaccination, and post-vaccination (breakthrough) SARS-CoV-2 infections. Methods: Retrospective electronic medical record data were analyzed from 907 adults with presumed COVID-19 seen between March 16, 2020 and January 7, 2021. Data included demographics, comorbidities, medications, vital signs, laboratory tests, pulmonary function tests, patient disposition, and co-infections. The overdispersed data (aod) R package was used to create a logit model using COVID-19 diagnosis by PCR as the dichotomous outcome variable. Univariate, conventional multivariate and elastic net machine learning were used to analyze data. Results: Male gender, elevated baseline temperature, and respiratory rate predicted COVID-19 diagnosis. Eosinopenia, neutrophilia, and lymphocytosis were also associated with COVID-19 diagnosis. However, asthma and COPD diagnoses were not associated with SARS-CoV-2 PCR positive test. Male gender, low oxygen saturation, and lower forced expiratory volume in 1 s (FEV1 ) were associated with higher hospital referral. Conclusions: CRD patients with acute respiratory symptoms in the ambulatory setting were more likely to have COVID-19 if male, febrile and tachypneic. Patients with lower pre-morbid FEV1 and lower SPO2 are more likely to be referred to the hospital. A composite of vitals sigs and WBC differential help risk stratify CRD patients seeking care for presumed COVID-19. Highlights: A composite of vitals and labs stratify patients with presumed COVID-19 diagnosis. Gender, relative pyrexia and tachypnea may predict SARS-CoV-2 PCR positive tests. Hospital referrals are influenced by oxygen saturation and pre-COVID spirometry.